Copper electroplating liquid and application thereof

By adding stress regulators and other additives to the copper plating solution to adjust the grain structure, the stress problem in the copper plating layer is solved, and efficient and low-cost copper plating preparation is achieved, which improves the performance and stability of solar cell cells.

CN120350413APending Publication Date: 2025-07-22SUZHOU SUNWELL NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510438873.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

It is difficult for existing copper plating solution to effectively control the internal stress of the copper plating under high current density, resulting in the plating easily cracking and falling off, affecting the efficiency and stability of solar cell cells, and low electroplating efficiency.

Method used

Copper electroplating solution containing stress regulators such as thiourea, boric acid, nickel salt or cobalt salt is used, combined with aligning agent, accelerator and leveling agent, and reduces the stress in the plating layer by adjusting the grain structure and deposition method, which is suitable for high-current density electroplating.

Benefits of technology

Obtain copper plating with low internal stress, high adhesion and good appearance at high current density to improve electroplating efficiency, meet the high-efficiency and low-cost production requirements of the photovoltaic industry, and extend the service life of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a copper electroplating solution and application thereof. The invention relates to a copper electroplating solution, which comprises the following raw materials: 20-250g / L of copper sulfate; 4-98g / L of sulfuric acid; the concentration of chloride ions is 50 to 300 mg / L; 0.5 g / L to 10 g / L of a displacement agent; 0.2-15 g / L of an accelerator; 2 to 20 mg / L of a leveling agent; 5-50 mg / L of a stress regulator; wherein the stress regulator comprises one or a combination of more of thiourea, boric acid, nickel salt and cobalt salt. The copper electroplating liquid can be used for rapidly electroplating and preparing a copper plating layer under the condition of high current density, and meanwhile, the obtained copper plating layer has remarkably lower internal stress, good adhesive force and better appearance, and is suitable for being applied to electrode preparation of solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper electroplating solution and its application, particularly a copper electroplating solution for copper grid lines or leadframes of solar cell wafers. Background Art

[0002] The photovoltaic industry is an important field for realizing the transformation to green energy. The efficiency and stability of solar cells directly affect the performance of the entire photovoltaic power generation system. In the manufacturing process of solar cells, the copper electroplating process is one of the key technologies for constructing highly conductive circuits, mainly used for preparing conductive components such as grid lines and back electrodes. Compared with the traditional silver paste printing process, the copper electroplating process has significant advantages such as low cost, excellent conductivity, and high resource utilization rate, and thus has gradually become the mainstream choice in the photovoltaic industry.

[0003] Most of the copper electroplating solutions for the existing copper electroplating process in the photovoltaic industry adopt a copper sulfate - sulfuric acid system, supplemented with additives such as brighteners to improve the coating quality. These additives can optimize the appearance and physical properties of the coating to a certain extent, but their ability to control internal stress is limited. Especially under high current density and high - speed deposition conditions, the coating is prone to accumulate large residual stress. In addition, some additives may introduce metal impurities or unstable chemical substances, thereby affecting the stability and environmental friendliness of the electroplating solution, which does not meet the requirements of the photovoltaic industry for process greening.

[0004] During the copper electroplating process of solar cell wafers, the problem of internal stress in the coating has an important impact on the performance of the cell wafers. Coatings with high internal stress are prone to cause wafer bending, coating cracking or even peeling of the cell wafers, which not only reduces the conversion efficiency of the cell wafers but also affects their long - term stability and reliability. Especially in the context of the gradual popularization of high - power - density and thin - film solar cell wafers, the control of internal stress during the electroplating process has become particularly important.

[0005] For example, a known copper electroplating solution includes the following components: copper sulfate 15 - 250 g / L, sulfuric acid 10 - 100 g / L, structure - guiding agent 0.2 - 20 g / L, catalyst 0.2 - 10 g / L, defoamer 0.2 - 10 g / L. This copper electroplating solution adds a structure - guiding agent, which promotes the deposition of copper along a fixed crystal orientation, making the growth rate in the length direction faster than that in the width direction, forming multiple closely arranged nanowires at the opening. The nanowires agglomerate to form copper grid lines, improving the aspect ratio of the copper grid lines and at the same time improving the flexibility of the copper grid lines. However, this copper electroplating solution cannot solve the problem of internal stress in the copper coating on solar cell wafers. In addition, the current density during the electroplating process is only 1.5 - 2.5 Asd, and the electroplating time required is relatively long, especially for solar cell wafers with a relatively thick coating, the electroplating efficiency is low.

[0006] The above information disclosed in the background section is only used to enhance the understanding of the background of the present application, and thus it may include information that does not constitute the prior art known to those of ordinary skill in the art. Summary of the Invention

[0007] In view of the above problems, an object of the present invention is to provide a copper electroplating solution that can rapidly electroplate and prepare a copper coating under high current density conditions, and at the same time, the obtained copper coating has significantly lower internal stress, good adhesion and better appearance, and is suitable for application in the preparation of electrodes of solar cell wafers.

[0008] Another object of the present invention is to provide an application of the copper electroplating solution in the preparation of solar cell wafers or lead frames, especially facilitating the obtaining of copper grid lines of solar cell wafers with lower internal stress under high current density, improving the electroplating efficiency of solar cell wafers and reducing the manufacturing cost.

[0009] The first aspect of the present invention provides a copper electroplating solution, the raw materials of which include the following components:

[0010]

[0011] Among them, the stress regulator includes one or more combinations selected from thiourea, boric acid, nickel salts and cobalt salts.

[0012] In one embodiment, the content of copper sulfate can be, for example: 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, 200 g / L, 220 g / L, 240 g / L or 250 g / L. In a preferred embodiment, the content of copper sulfate is 20 - 200 g / L. In a more preferred embodiment, the content of copper sulfate is 100 - 200 g / L.

[0013] In one embodiment, the content of sulfuric acid can be, for example: 4 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 95 g / L or 98 g / L. In a preferred embodiment, the content of sulfuric acid is 10 - 50 g / L. In a more preferred embodiment, the content of sulfuric acid is 20 - 50 g / L. In a further preferred embodiment, the content of sulfuric acid is 30 - 50 g / L.

[0014] In one embodiment, the chloride ion content can be, for example: 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 130 mg / L, 140 mg / L, 150 mg / L, 160 mg / L, 170 mg / L, 180 mg / L, 190 mg / L, 200 mg / L, 220 mg / L, 240 mg / L, 250 mg / L, 260 mg / L, 270 mg / L, 280 mg / L, 290 mg / L or 300 mg / L. In a preferred embodiment, the chloride ion content is 100 - 250 mg / L. In a more preferred embodiment, the chloride ion content is 150 - 200 mg / L.

[0015] In one embodiment, the chloride ions are added in the form of HCl and / or NaCl.

[0016] In one embodiment, the content of the leveling agent can be, for example: 0.5 g / L, 0.75 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L or 10 g / L. In a preferred embodiment, the content of the leveling agent is 1 - 10 g / L. In a more preferred embodiment, the content of the leveling agent is 1 - 5 g / L.

[0017] In one embodiment, the leveling agent includes one or more combinations selected from polyethylene glycol 400 - 10000, nonylphenol polyoxyethylene ether OP - 4 - OP - 12, and octylphenol polyoxyethylene ether NP - 4 - NP - 12. Among them, the polyethylene glycol uses polyethylene glycol with a weight average molecular weight of 400 - 10000, such as: polyethylene glycol 400, polyethylene glycol 2000, polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000 or polyethylene glycol 10000; the nonylphenol polyoxyethylene ether includes nonylphenol polyoxyethylene ether with specifications of OP - 4, OP - 7, OP - 9, OP - 10 and OP - 12; the octylphenol polyoxyethylene ether includes octylphenol polyoxyethylene ether with specifications of NP - 4, NP - 7, NP - 9, NP - 10 and NP - 12. In a specific and preferred embodiment, the leveling agent includes polyethylene glycol 2000.

[0018] In one embodiment, the content of the accelerator can be, for example: 0.2 g / L, 0.5 g / L, 0.75 g / L, 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L or 15 g / L. In a preferred embodiment, the content of the accelerator is 0.2 - 12 g / L. In a more preferred embodiment, the content of the accelerator is 2 - 10 g / L. In a further preferred embodiment, the content of the accelerator is 5 - 10 g / L.

[0019] In one embodiment, the accelerator includes sodium bis(3-sulfopropyl) disulfide and / or bis(3-sulfopropyl) disulfide.

[0020] In one embodiment, the content of the leveling agent can be, for example: 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L. In a preferred embodiment, the content of the leveling agent is 2 - 15 g / L. In a more preferred embodiment, the content of the leveling agent is 5 - 12 g / L. In a further preferred embodiment, the content of the leveling agent is 5 - 10 g / L.

[0021] In one embodiment, the leveling agent includes one or more combinations selected from sodium thiazoline-2-yl propane sulfonate (SH110), polyethyleneimine alkyl compound (GISS), fatty amine ethoxysulfonate (AESS), polyethyleneimine alkyl salt (PN). In a specific and preferred embodiment, the leveling agent includes sodium thiazoline-2-yl propane sulfonate (SH110) or polyethyleneimine alkyl compound (GISS).

[0022] In one embodiment, the content of the stress regulator can be, for example: 5 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L. In a preferred embodiment, the content of the stress regulator is 20 - 50 mg / L. In a more preferred embodiment, the content of the stress regulator is 20 - 40 mg / L. In a specific and preferred embodiment, the stress regulator includes thiourea.

[0023] In a preferred embodiment, the copper electroplating solution is suitable for preparing a copper grid line on a solar cell wafer or a copper coating on a lead frame at a high current density above 10 Asd.

[0024] The second aspect of the present invention provides an application of the copper electroplating solution in the preparation of solar cell wafers or lead frames.

[0025] In a preferred embodiment, at a high current density above 10 Asd, the copper electroplating solution is used to prepare a copper electrode on a solar cell wafer. Specifically, the copper electroplating solution is used to electroplate and prepare a copper grid line electrode on a solar cell wafer.

[0026] The present invention adopts the above scheme and has the following advantages:

[0027] For the copper electroplating solution of the present invention, a stress regulator is introduced. Through the synergistic effect of the stress regulator with the leveling agent, accelerator, and leveling agent, the internal stress of the coating is significantly reduced by adjusting the grain structure and deposition mode; this plating solution exhibits excellent deposition uniformity under high current density (allowing a high current density above 10 Asd) and high-speed electroplating conditions. The obtained coating has low internal stress, high adhesion, good appearance, and good electrical conductivity. The plating solution provided by the present invention has the characteristics of environmental friendliness and strong stability, meeting the requirements of the photovoltaic industry for high-efficiency and low-cost production, while improving the performance and service life of solar cells. At the same time, this formulation can also be applied to the copper electroplating process of semiconductors such as lead frames. Description of the Drawings

[0028] In order to more clearly illustrate the technical solutions of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0029] Figure 1 It is a photograph of the compatibility test device under high current density in the present invention.

[0030] Figure 2 It is a photograph of one of the test results of the compatibility test under high current density in the embodiments of the present invention. Detailed Embodiments

[0031] The following elaborates on the preferred embodiments of the present invention to make the advantages and features of the present invention more easily understood by those skilled in the art. It should be noted here that the description of these embodiments is for helping to understand the present invention, but does not constitute a limitation to the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] This embodiment provides a highly low-stress electroplated copper plating solution specifically for the photovoltaic industry, especially suitable for preparing the front grid electrodes and back electrodes of solar cell wafers that allow for the preparation at high current densities. Since the solar cell has no open structure and there is no need to specifically add a dedicated carrier in the formulation, this embodiment relates to an additive formulation capable of achieving high-speed electroplating from matte copper to semi-bright copper (allowing high current densities above 10 Asd).

[0033] A copper electroplating solution, the raw materials of which include the following components: copper sulfate 20 - 250 g / L; sulfuric acid 4 - 98 g / L; chloride ions 50 - 300 mg / L; leveling agent 0.5 - 10 g / L; accelerator 0.2 - 15 g / L; brightener 2 - 20 mg / L; stress regulator 5 - 50 mg / L; and the solvent is water. Among them, the stress regulator includes one or more combinations selected from thiourea, boric acid, nickel salts, and cobalt salts. By using sulfur-containing compounds or metal complexes (nickel and cobalt metal complexes), compounded with leveling agents and other components in the formulation and cooperating synergistically, the internal stress of the coating is significantly reduced by adjusting the grain structure and deposition mode. This plating solution exhibits excellent deposition uniformity under high current density and high-speed electroplating conditions, and the obtained coating has low internal stress, high adhesion, and good electrical conductivity. This copper electroplating solution also has the characteristics of environmental friendliness and strong stability, meeting the requirements of the photovoltaic industry for high-efficiency and low-cost production, while improving the performance and service life of solar cells. At the same time, this formulation can also be applied to the copper electroplating process of advanced semiconductors such as lead frames (Leadframe).

[0034] The chloride ions include one or more of HCl and NaCl, and are added to the solvent in the form of HCl, NaCl, etc. and mixed with other components of the copper electroplating solution.

[0035] The leveling agent includes one or more of polyethylene glycol 400 - 10000, nonylphenol polyoxyethylene ether OP-4 - OP-12, and octylphenol polyoxyethylene ether NP-4 - NP-12.

[0036] The accelerator includes one or more of sodium polydithiopropane sulfonate SPS and sodium polydithiopropane sulfonate SP.

[0037] The brightener includes one or more of SH110, GISS, AESS, PN, and SLP.

[0038] The following further elaborates on the present invention with specific embodiments.

[0039] Examples 1 - 6 and Comparative Examples 1 - 4

[0040] The copper electroplating solutions of Examples 1 to 6 and Comparative Examples 1 to 4 use deionized water as a solvent, and the following components are added and mixed evenly: 200 g / L of copper sulfate, 90 g / L of concentrated sulfuric acid (specific gravity at 20 °C is 1.84), 190 mg / L of concentrated hydrochloric acid (specific gravity of concentrated hydrochloric acid at 20 °C is 1.18, containing about 183 mg / L of chloride ions), 10 mg / L of an accelerator (sodium poly(dithiopropane sulfonate) SPS), and 1 g / L of a leveling agent (polyethylene glycol 2000). Among them, for the specific components and dosages of the leveling agent and stress regulator, refer to Table 1 below.

[0041] The following performance tests were carried out on the prepared copper electroplating solutions.

[0042] I. Internal stress of the coating

[0043] Specimen preparation: Using the copper electroplating solutions of Examples 1 to 6 and Comparative Examples 1 to 4, electroplate the test pieces to obtain electroplated test pieces with a coating of a preset thickness. The coating of the preset thickness is 12 micrometers, and the test pieces are battery wafers with a copper seed layer.

[0044] Test method: Use the standard test method ASTM B975-15 for measuring the internal stress of the metal coating by the strip evaluation method. Fix the electroplated test piece on the test instrument, and the distance value between the two feet of the electroplated test piece can be read. Substitute this distance value into the formula to calculate the internal stress of the coating.

[0045] The test results are shown in Table 1.

[0046] Table 1

[0047] Specimen Leveling agent Stress regulator Internal stress of coating / psi Comparative example 1 GISS 10 mg / L Thiourea 2 mg / L 915.9 Example 1 GISS 10 mg / L Thiourea 5 mg / L 385.1 Example 2 GISS 10 mg / L Thiourea 20 mg / L 125.6 Example 3 GISS 10 mg / L Thiourea 50 mg / L 153.7 Comparative example 2 GISS 10 mg / L Thiourea 100 mg / L 822.7 Comparative example 3 SH110 10 mg / L Thiourea 2 mg / L 922.1 Example 4 SH110 10 mg / L Thiourea 5 mg / L 407.2 Example 5 SH110 10 mg / L Thiourea 20 mg / L 139.4 Example 6 SH110 10 mg / L Thiourea 50 mg / L 178.3 Comparative example 4 SH110 10 mg / L Thiourea 100 mg / L 746.3

[0048] The results show that the dosage of the stress regulator has a significant impact on the internal stress of the coating; if the dosage of the stress regulator is too small, the internal stress of the coating may be large, especially when the grains are large and the crystallization is rough during the metal deposition process. At this time, the coating may bear high compressive stress or tensile stress, resulting in uneven coating quality, easy generation of cracks, and poor adhesion of the coating; if the stress regulator is used in excess, it may cause the metal deposition in the coating to be too fast, and the grain growth during the deposition process is restricted, resulting in a large tensile stress accumulated inside the coating. This excessive tensile stress will cause cracks or peeling of the coating, affecting the adhesion and durability of the coating. In addition, the synergistic combination of different leveling agents and stress regulators will also have a great impact on the internal stress of the coating.

[0049] It should also be noted that: compared with the known method of improving the internal stress of the coating by ultrasonic assistance (such as placing the electroplating bath in an ultrasonic bath), in this embodiment, without additional ultrasonic assistance, by using the above copper electroplating solution and directly adopting the conventional electroplating method, a copper coating with significantly lower internal stress can be obtained.

[0050] II. Detection of Coating Appearance and Adhesion

[0051] Appearance detection standard: Visually inspect that the copper plating surface shows a pure copper metallic luster, is free of contamination, has a uniform color without impurities, and the coating has no defects such as pinholes, pockmarks, peeling, or blackening.

[0052] Adhesion inspection standard: Use the cross - cut tape adhesion method and the scratch method. After scratching the copper plating surface with a knife, there is no peeling or delamination on the copper plating surface; when sticking tape at the scratched area, there is no peeling or delamination.

[0053] See Table 2 for the test results.

[0054] Table 2

[0055]

[0056]

[0057] It can be seen from Table 2 that if the dosage of the stress regulator is too small, the internal stress of the coating may be relatively large, especially when the grains are large and the crystallization is relatively rough during the metal deposition process. At this time, the coating may withstand a relatively high stress, resulting in non - uniform coating quality, easy generation of cracks, and poor adhesion of the coating; if the stress regulator is used in excess, it may cause the metal in the coating to deposit too fast, and the growth of grains during the deposition process is restricted, resulting in a large amount of stress accumulated inside the coating. This excessive tensile stress will cause cracks or peeling in the coating, affecting the adhesion and durability of the coating.

[0058] III. Test of Compatibility under High Current Density

[0059] Use Figure 1 the Hall cell test tool shown in the figure, apply the test condition of 5A for 1 minute, use the copper electroplating solutions of Examples 1 - 6, and after observing the struck - down samples, confirm that the copper electroplating solutions of Examples 1 - 6 can be compatible with the application window of current densities of > 2 - 20 + Asd. The application window of high current density (the maximum compatible high current density can reach 20 Asd) allows, under the requirement of a certain electroplated copper thickness, the electroplating time to be greatly shortened, which is beneficial to the utilization rate of relevant equipment and sites.

[0060] It can be understood that the same or similar parts in the above - mentioned embodiments can be referred to each other, and for the content not detailed in some embodiments, reference can be made to the same or similar content in other embodiments.

[0061] As shown in this specification and the claims, the terms "comprising" and "including" merely indicate the inclusion of the specifically identified steps and elements, which do not constitute an exclusive listing, and a method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the related listed items.

[0062] The endpoints and any values in the ranges disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, between the endpoints of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0063] If a numerical range is recited herein, unless otherwise stated, the range is intended to include its endpoints and all integers and decimals within the range.

[0064] The above embodiments are only for illustrating the technical concept and features of the present invention, and are a preferred embodiment. The purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and the protection scope of the present invention cannot be limited thereby. Any equivalent transformation or modification made according to the principle of the present invention should be covered within the protection scope of the present invention.

Claims

1. A copper electroplating solution, characterized in that, Its raw materials include the following components: Among them, the stress regulator includes a combination of one or more selected from thiourea, boric acid, nickel salts and cobalt salts.

2. The copper electroplating solution according to claim 1, wherein, The content of the stress regulator is 20 - 50 mg / L.

3. The copper electroplating solution according to claim 1, wherein, The content of the copper sulfate is 20 - 200 g / L; and / or, the content of the sulfuric acid is 10 - 50 g / L; and / or, the content of the leveling agent is 1 - 10 g / L; and / or, the content of the accelerator is 0.2 - 12 g / L.

4. The copper electroplating solution according to claim 1, characterized in that, The chloride ions are added in the form of HCl and / or NaCl.

5. The copper electroplating solution according to claim 1, characterized in that, The leveling agent includes a combination of one or more selected from polyethylene glycol 400 - 10000, nonylphenol polyoxyethylene ether OP-4 - OP-12, octylphenol polyoxyethylene ether NP-4 - NP-12.

6. The copper electroplating solution according to claim 1, characterized in that, The accelerator includes sodium bis(propylsulfonyl) disulfide and / or bis(propylsulfonyl) disulfide.

7. The copper electroplating solution according to claim 1, wherein The brightener includes a combination of one or more selected from sodium thiazolinyl propanesulfonate, polyethyleneimine alkyl compounds, fatty amine ethoxysulfonates and polyethyleneimine alkyl salts.

8. The copper electroplating solution according to claim 1, wherein The copper electroplating solution is suitable for preparing a copper grid line on a solar cell wafer or a copper coating on a lead frame at a high current density above 10 Asd.

9. Use of a copper electroplating solution according to any one of claims 1 to 8 in the preparation of a solar cell wafer or a lead frame.

10. The application according to claim 9, characterized in that, At a high current density above 10 Asd, the copper electroplating solution is used to prepare a copper electrode on a solar cell wafer.